Topical preparations to reduce SARS‐CoV‐2 aerosolization in head and neck mucosal surgery - Parhar, Harman S. (Head Neck, 2020)
AIM: The COVID‐19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has put health care workers at risk when exposed to aerosolized viral particles during upper airway mucosal surgery. The objective of this review was to discuss topical preparations that could be utilized preoperatively to help to decrease viral load and potentially reduce the risks of viral transmission. METHODS: A PubMed/MEDLINE database review of articles was performed querying topical preparations with virucidal activity against coronaviruses. RESULTS: Povidone‐iodine (PVP‐I) solutions ranging from 0.23% to 7% have been found to demonstrate highly effective virucidal activity against a broad range of viruses including several coronaviruses responsible for recent epidemics including SARS‐CoV‐1 and MERS‐CoV. CONCLUSIONS: While specific evidence regarding SARS‐CoV‐2 is lacking, PVP‐I‐based preparations have been successfully demonstrated to reduce viral loads of coronaviruses. They are relatively safe to use in the upper airway and may reduce risk of SARS‐CoV‐2 aerosolization during upper airway mucosal surgery.